Kesenjangan Upah Antargender di Indonesia: Bukti Empiris di Sektor Manufaktur - Laili, Martesa Husna; Damayanti, Arie (UI Scholars Hub, 2018)
Theoretically, in the labor market without discrimination, wages should be paid according to productivity. Unlike other studies that use worker level data, this study will identify gender wage discrimination using firm-level data. Using Industrial Survey Data in 1996 and 2006, the gender wage ratio and gender productivity ratio were estimated simultaneously using the nonlinear seemingly unrelated regression (NLSUR) with least square estimator. We find that there is wage discrimination against women in the manufacturing sector. After disaggregating the firms by trade orientation, we show that wage discrimination against women occurs in non-exporting firms. While in exporting firms there is no wage discrimination.